Digital Readiness Of Msmes In The Industry 4.0 Era: A Study On Culinary Sector Msmes In Tuntang Sub-District, Semarang Regency - Hardian, Hardian; Mohammad Halilintar (PT. ALHAFI BERKAH INDONESIA, 2025)
This study examines the digital readiness of Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector in Tuntang District, Semarang Regency in facing the Industry 4.0 era. The research employed a descriptive quantitative approach, involving 75 culinary MSME owners through questionnaires and structured interviews. The results show that the majority of culinary MSMEs in Tuntang District are at the